Role of dietary and nutritional interventions in ceramide-associated diseases - Shengnan Wang; Zihui Jin; Biyu Wu; Andrew J. Morris; Pan Deng (Journal of Lipid Research)
Ceramides are important intermediates in sphingolipid metabolism and serve as signaling molecules with independent biological significance. Elevated cellular and circulating ceramide levels are consistently associated with pathological conditions including cardiometabolic diseases, neurological diseases, autoimmune diseases, and cancers. Although pharmacological inhibition of ceramide formation often protects against these diseases in animal models, pharmacological modulation of ceramides in humans remains impractical. Dietary interventions including the Mediterranean diet, lacto-ovo-vegetarian diet, calorie-restricted diet, restriction of dairy product consumption, and dietary supplementation with polyunsaturated fatty acids, dietary fibers, and polyphenols, all have beneficial effects on modulating ceramide levels. Mechanistic insights into these interventions are discussed. This article reviews the relationships between ceramides and disease pathogenesis, with a focus on dietary intervention as a viable strategy for lowering the concentration of circulating ceramides.